Conservation letters (Blackwell Pub., 2008)
A scientific journal publishing empirical and theoretical research with immediate implications for the conservation of biological diversity worldwide. Contents include letters, mini-reviews, and policy perspectives related to all biomes, ecosystems, and cultural settings.